EXAMINING PRODUCT QUALITY, ONLINE REVIEWS, AND RATINGS ON PURCHASE DECISION VIA CUSTOMER TRUST: EVIDENCE FROM WARDAH PRODUCTS - Putri Miranda; Filda Rahmiati; Intan Syafinatun Nida (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2025)
Skin care has become a basic need for society. Using skin care believed to make the skin more well-maintained. It is certain that there will be an increase in demand for quality skin care products. Wardah is one of the brands that competes in the beauty industry. Nowadays, many consumers look at online reviews and ratings before deciding to buy a product. Therefore, this research was conducted to study product quality, online reviews, and online ratings on purchase decisions through consumer trust. This research uses a quantitative analysis method obtains data from questionnaires distributed online, provided that respondents have experience or use Wardah products. This research uses a nonprobability sampling technique known as purposive sampling. This research obtained a total of 143 complete respondents. SMARTPLS-SEM 4 software was used to analyze data and test hypotheses. The research results show that product quality, online ratings, and consumer trust have a significant influence on purchase decisions. However, the results of online review research do not have a significant effect on purchase decisions. After being mediated by customer trust, only product quality has a significant influence on purchase decisions. Online ratings and online reviews do not have a significant influence on purchase decisions.